Ukraine and the EU: Prospects and Challenges on the Road to Integration - Soloviova, A.; Fomin, A. V.; Соловйова, А.; Фомін, А. В. (Чорноморський національний університет імені Петра Могили, 2025)
This article examines Ukraine’s journey toward European Union integration, focusing on the prospects and challenges that lie ahead. Ukraine’s desire for EU membership represents not only a strategic shift but also a complex transformation requiring significant reforms in governance, economics, and security. The article explores the political challenges, such as aligning Ukraine’s legal and administrative systems with EU standards. It also discusses the economic disparities between Ukraine and EU nations, emphasizing the need for economic stabilization and growth to bridge these gaps and ensure long-term resilience. Additionally, the war caused by Russian aggression presents serious security concerns, necessitating strong international cooperation to achieve stability. So the purpose of the study is to examine and critically evaluate Ukraine’s journey toward European Union membership, paying particular attention to the potential opportunities and obstacles that lie ahead. By analyzing Ukraine’s efforts to meet EU standards, implement political and economic reforms, and align with European values, the article aims to shed light on the progress Ukraine has made on its path to integration. This article explores that despite these challenges, the potential benefits of EU integration for Ukraine are substantial. Closer ties with the EU can foster economic growth, attract foreign investment, and expand trade opportunities, which are critical for Ukraine’s post-war recovery. Moreover, the EU’s framework can support political stability and promote governance reforms, essential for Ukraine’s democratic development. Membership could also enhance the EU’s influence in Eastern Europe, contributing to regional stability and strengthening European unity. By analyzing both the obstacles and opportunities, this article provides a balanced overview of Ukraine’s integration process, highlighting that while the path is challenging, the potential rewards make the journey worthwhile for both Ukraine and the EU. The study underscores that a committed and collaborative approach can help transform Ukraine’s vision of EU membership into a reality, ultimately contributing to greater stability and prosperity in Europe.

Ця стаття досліджує шлях України до інтеграції до Європейського Союзу, зосереджуючись на перспективах і викликах, що стоять попереду. Бажання України стати членом ЄС є не лише стратегічним зрушенням, а й складною трансформацією, що вимагає значних реформ у сфері управління, економіки та безпеки. У статті розглядаються політичні виклики, зокрема узгодження правової та адміністративної систем України зі стандартами ЄС. Також обговорюються економічні розбіжності між Україною та країнами ЄС, підкреслюючи потребу в економічній стабілізації та зростанні для подолання цих розривів і забезпечення довгострокової стійкості. Крім того, війна, спричинена агресією Росії, створює серйозні проблеми безпеки, що потребують міцної міжнародної співпраці для досягнення стабільності. Отже, метою дослідження є вивчення та критична оцінка шляху України до членства в Європейському Союзі з особливим акцентом на потенційні можливості та перешкоди, що чекають попереду. Аналізуючи зусилля України щодо відповідності стандартам ЄС, впровадження політичних та економічних реформ і дотримання європейських цінностей, стаття прагне висвітлити прогрес, якого Україна досягла на шляху до інтеграції. В статті зазначено, що незважаючи на ці виклики, потенційні вигоди від інтеграції з ЄС для України є значними. Тісніші зв’язки з ЄС можуть сприяти економічному зростанню, залученню іноземних інвестицій і розширенню торговельних можливостей, що є критично важливими для відновлення України в післявоєнний період. Крім того, рамкова структура ЄС може підтримувати політичну стабільність і сприяти реформам управління, необхідним для демократичного розвитку України. Членство також може посилити вплив ЄС у Східній Європі, сприяючи регіональній стабільності та зміцненню європейської єдності. Аналізуючи як перешкоди, так і можливості, ця стаття надає збалансований огляд процесу інтеграції України, підкреслюючи, що, хоча шлях є складним, потенційні здобутки роблять його вартим зусиль як для України, так і для ЄС. Дослідження акцентує увагу на тому, що відданий і спільний підхід може допомогти втілити бачення України щодо членства в ЄС у реальність, що зрештою сприятиме стабільності та процвітанню в Європі.
Україна та ЄС: перспективи та виклики на шляху інтеграції
Keywords: Ukraine; the European Union (EU); euro integration; European values; Ukraine’s EU membership; Україна; Європейський Союз (ЄС); євроінтеграція; європейські цінності; членство України в ЄС